The Perspicuity of the Scriptures: Presupposition, Principle or Phantasm - Kristian Brackett (Kairos (English Ed.))
The doctrine of the perspicuity of the Scriptures was clearly articulated and strongly defended by the Reformers. Evangelical Christians today also need to reaffirm and defend this biblical doctrine. This article addresses the importance of this doctrine and looks at different definitions of this doctrine as well as its limitations. In the second part, theological and biblical evidence supporting the perspicuity of the Scriptures is presented. In the final section, the author suggests an answer to the question of whether the perspicuity of the Scriptures is a presupposition brought to the biblical text or a principle of interpretation.